Topological encounters in biodiversity conservation: Making and contesting maps in the Colombian high Andean páramos - Castillo-Estupiñan, Camilo (Frontiers in Ecology and Evolution, 2023)
Páramos are one of the flagship ecosystems in the Northern Andes: the provision of water for millions of people in that region depends on these unique high mountains located above 3500mts of altitude. Besides, they are also the refuge of a rich biodiversity unique in the world whose conservation has become central over the last years. Humans have also inhabited some páramos, as is the case for campesino communities, who in the case of Sumapaz region in central Colombia, found in páramos páramos a safe place after fleeing and suffering political violence during the 20th century. Since 2010, the Colombian government, following previous legislation and court sentences, declared páramos as “strategic ecosystems”, making their conservation an important part of the environmental policy in the country. This was advanced through map-making as the tool to define clear-cut limits for human use, prohibiting mining, agriculture and livestock in spaces demarcated as páramos. However, this made incompatible the conservation of the policy with the presence of campesinos living in páramos. Since then, their conservation in the Sumapaz region has been a conflictive matter about what kind of páramos and biodiversity should be allowed and enacted in Colombia. As part of a two year multisited ethnography with geographers and campesino communities in Sumapaz páramo, I develop a topological approach to study map-making practices in the context of biodiversity conservation. This, I argue, can be a way to understand the diverse relations between humans and natures as partial space configurations that shape conservation practice and its forms of politics. With this social sciences contribution, I extend the map-making discussions in conservation that seek to open taken for granted notions of space that limit the possibilities of conservation for socioenvironmental change